CO2 hydrogenation to methanol over Rh/In2O3 catalyst - Wang, Jing; Sun, Kaihang; Jia, Xinyu; Liu, Chang-jun (Catalysis today, 2021)
[Display omitted] •Rh/In2O3 catalyst shows high activity for hydrogenation of CO2 to methanol.•Rh/In2O3 catalyst possesses similar methanol selectivity (>70 %) as In2O3 under 275 °C.•Highly dispersed Rh catalyst enhances the dissociative adsorption and spillover of hydrogen.•The Rh loading promotes the formation of surface oxygen vacancy of In2O3.•CO2 adsorption and activation are enhanced by surface oxygen vacancy of In2O3. CO2 hydrogenation to methanol is of great significance for the emission control and utilization of CO2. In this work, the Rh/In2O3 catalyst with high Rh dispersion was prepared by deposition-precipitation method. The catalyst characterization demonstrates that the highly dispersed Rh species promotes the dissociative adsorption and spillover of hydrogen, which further enhances not only the formation of surface oxygen vacancy of In2O3 but also CO2 adsorption and activation. Enhanced activity was thereby achieved for selective hydrogenation of CO2 to methanol. A CO2 conversion of 17.1 % with methanol selectivity of 56.1 %, corresponding to a methanol space time yield (STY) up to 0.5448 gMeOH h−1 gcat−1, has been obtained under 300 °C, 5 MPa, 76/19/5 of H2/CO2/N2 (molar ratio) and 21,000 cm3 h−1 g−1 of gas hourly space velocity. Under the same reaction condition, the CO2 conversion is only 9.4 % with a methanol STY of 0.3402 gMeOH h−1 gcat−1 over In2O3. The methanol selectivity can be even higher than 70 % at the reaction temperatures below 275 °C for Rh/In2O3 catalyst.